2005
DOI: 10.3148/66.4.2005.252
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Price, Amounts of Saturated and Trans Fats, and Nutrient Content Claims on Margarines and Oils

Abstract: The findings for margarines are of particular concern for lower income groups for whom budgetary constraints result in the purchase of lower priced foods, and also raise important questions about the usefulness of nutrient content claims in guiding food selections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 7 publications
0
20
0
3
Order By: Relevance
“…In developed countries, margarines often contain trans fatty acids (Albers et al, 2008;Skeaff, Gowans, Skeaff, & Gowans, 2006) and studies have found that levels of these fats are inversely related to product price (Albers et al, 2008;Ricciuto, Ip, & Tarasuk, 2005). Trans fatty acids have been associated with poorer cognitive performance in adults (Morris et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In developed countries, margarines often contain trans fatty acids (Albers et al, 2008;Skeaff, Gowans, Skeaff, & Gowans, 2006) and studies have found that levels of these fats are inversely related to product price (Albers et al, 2008;Ricciuto, Ip, & Tarasuk, 2005). Trans fatty acids have been associated with poorer cognitive performance in adults (Morris et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…26 Second, some foods with low TFA levels are costlier, which will be felt more by consumers with a low socioeconomic status. 17,24,38 Ricciuto et al 24 found that some margarine companies in Canada offered products with a low TFA level while continuing to sell products with a high level at a lower price. Thus, price-conscious consumers would be more likely to consume the less healthy product, thereby increasing their risk of diet-related chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Related cardiovascular and metabolic health concerns (Ascherio, Katan, Zock, Stampfer, & Willett, 1999;Kuller, 2006;Rader, 2007;Stender & Dyerberg, 2004) have led to the development of margarines, spreads, and food products that are lower in saturated and trans fats, including 'trans fat free' and 'low in saturated fats' preparations. Marketplace surveys, however, indicate that there is an inverse relationship between the price of margarines and the content of saturated and trans fats that they contain (Albers, Harnack, Steffen, & Jacobs, 2008;Ricciuto & Tarasuk, 2005). Thus, currently available products that are lower in saturated and trans fats tend to cost more, and this may be a significant barrier to their use by price-conscious, and lower income consumers.…”
Section: Introductionmentioning
confidence: 87%